(untitled) (World Economics and Finance Bulletin, 2022)
Female entrepreneurs contribute substantially to economic growth in Asia, particularly in Malaysia. This article presents a comprehensive review of female entrepreneurs, focusing on created opportunities and business environment in this country. Entrepreneurs must be seen as essential for growth, job creation and social progress and the virtues of small business. Therefore, governments and non-governments should put their efforts more strongly to ensure that women entrepreneurs are well supported and enhanced